Lack of Immune Response to Mouse IgG in Hemophilia A Patients Treated Chronically with Monoclate®, a Monoclonal Antibody Affinity Purified Factor VIII Preparation - Davis, Hugh M; Brown, Susan K; Nash, David W; Pennetti, Aniello M; Salzman, Phyllis M; Schreiber, Alian B; Haimovich, Joseph (Thrombosis and Haemostasis, 1990)
Hemophilia A is caused by factor VIII deficiency that historically has been treated with either a cryoprecipitate fraction of serum or factor VIII concentrate. Recently, the availability of affinity isolated factor VIII (Monoclate®) has allowed for a highly purified preparation for the chronic therapy of hemophilia A. This factor VIII preparation contains a trace quantity (<50 ng/ 100 I. U.) of mouse IgG. Immunoassays for the measurement of human IgG, IgJVl and IgE anti-mouse TgG antihody (HAMA) were developed and used to measure HAMA levels in hemophilia A patients undergoing chronic therapy with Monoclate® in three different clinical studies. Natural antibodies to mouse IgG were observed in patient sera prior to Monoclate® infusion. Data is presented demonstrating that induction of HAMA upon Monoclate® treatment does not occur. The low level of mouse IgG contained in Monoclate® appears to be below the threshold of immunogenicity. Most importantly, clinical symptoms related to hypersensitivity or anaphylaxis were never observed in any patient undergoing chronic therapy with Monoclate® in these clinical studies.